THE FITERAL METHOD OF WORD MEANING ANALYSIS WITH THE USE OF INFORMATION TECHNOLOGY - M. A. Novikova; M. G. Kulikova (Современная наука и инновации)
The article is devoted to the solution of the problem of improving the quality of wastewater treatment by improving the treatment facilities. The article deals with the main methods of purification and the quality indicators of sewage, a promising solution is proposed for the environmental problems of the region.